DIE-RNA: A Reproducible Strategy for the Digestion of Normal and Injured Pancreas, Isolation of Pancreatic Cells from Genetically Engineered Mouse Models and Extraction of High Quality RNA - Assi, Mohamad; Dauguet, Nicolas; Jacquemin, Patrick (Frontiers in Physiology, 2018)
The isolation of ribonucleic acid (RNA) suitable for gene expression studies is challenging in the pancreas, due to its high ribonuclease activity. This is even more complicated during pancreatitis, a condition associated with inflammation and fibrosis. Our aim was to implement a time-effective and reproducible protocol to isolate high quality RNA from specific pancreatic cell subtypes, in normal and inflammatory conditions. We used two genetically engineered mouse models (GEMM), Ela-CreER/YFP and Sox9-CreER/YFP, to isolate acinar and ductal cells, respectively. To induce pancreatitis, mice received a caerulein treatment (125 µg/kg) for 8 and 72 h. We alternatively used EGTA and calcium buffers that contain collagenase P (0.6 mg/mL) to rapidly digest the pancreas into individual cells. Most of the cells from normal and injured pancreas were single-dissociated, exhibited a round morphology and did not incorporate trypan blue dye. Cell suspensions from Ela- and Sox9-CreER/YFP pancreas were then sorted by flow cytometry to isolate the YFP-positive acinar and ductal cells, respectively. Sorted cells kept a round shape and emitted fluorescence detected by the 38 HE green fluorescence filter. RNA was isolated by column-based purification approach. The RNA integrity number (RIN) was high in sorted acinar cell fractions treated with or without caerulein (8.6 ± 0.17 and 8.4 ± 0.09, respectively), compared to the whole pancreas fraction (4.8 ± 1.1). Given the low number of sorted ductal cells, the RIN value was slightly lower compared to acini (7.4 ± 0.4). Quantitative-PCR experiments indicated that sorted acinar and ductal cells express the specific acinar and ductal markers, respectively. Additionally, RNA preparations from caerulein-treated acinar cells were free from significant contamination with immune cells RNA. We thus validated the DIE (Digestion, Isolation and Extraction)-RNA tool as a reproducible and efficient protocol to isolate pure acinar and ductal cells in vivo and to extract high quality RNA from these cells.